The problem of personality in the context of historic memory: Allusions to Chekhov in Rudkovsky’s comedy To live to the premiere - Ищук-Фадеева, Нина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The article addresses the semantic relations of Rudkovsky, a modern playwright, with Chekhov’s comedies. The self-consciousness of a person in Chekhov’s drama is directly connected with the historic memory, and this idea is interpreted in Rudkovsky’s works through the theatrical experiment, allowing the actresses to go through war as a personal experience, and for the audience – to set right “the joint” of time.